PENGARUHGROUP SIZE TERHADAP PENGAMBILAN KEPUTUSAN KELOMPOK Diah - Diah Nurayu Kusumawardani; Joevarian Joevarian; Nezza Nehemiah; Pramwidya Mazmur Novia; Putu Widiastiti Giri (Universitas Ahmad Dahlan, 2013)
AbstractPeople have to deal with problems on a daily basis. Problems mayappear both at the individual level and at the group level. Effective methods to deal with problems become essential. This paper questons ‘Does the number of people in a single group matter in effective problem solving? Previous studies have shown inconsistencies of results. This paper aims to find a cause-effect relationship between group size and the effectivity of problem solving wthin the group. There are two types of experimentalgroups with the total of 16 groups. The first eight consists of 4 people and the latter consists of 8 people within a group. One-tailed hypothesis stated that groups of 4 will perform better than groups of 8. Every group was given a same case to be solved. While the observed group dynamics differences existed, the results showed that the group of 4 is no better than the groups of 8 in terms of decision making effectivity. The results, will befurther discussed.Key word: Group Dynamic, Group Size, Decision Making Effectiveness